The Cambridge companion to the body in literature - Hillman, David, Ed; Maude, Ulrika, Ed (Cambridge companions to literature, 2015)
"This Companion offers the first systematic analysis of the representation of the body in literature. It historicizes embodiment by charting our evolving understanding of the body from the Middle Ages to the present day, and addresses such questions as sensory perception, technology, language and affect; maternal bodies, disability and the representation of ageing; eating and obesity, pain, death and dying; and racialized and posthuman bodies. This Companion also considers science and its construction of the body through disciplines such as obstetrics, sexology and neurology. Leading scholars in the field devote special attention to poetry, prose, drama and film, and chart a variety of theoretical understandings of the body"--